Glucosamine loaded injectable silk-in-silk integrated system modulate mechanical properties in bovine ex-vivo degenerated intervertebral disc model. (July 2015) - Murab, Sumit; Samal, Juhi; Shrivastava, Akshay; Ray, Alok Ranjan; Pandit, Abhay; Ghosh, Sourabh
Abstract: Injectable hydrogels offer a tremendous potential for treatment of degenerated intervertebral disc due to their ability to withstand complex loading, conforming precisely to the defect spaces and eliminating the need for invasive surgical procedures. We have developed an injectable hydrogel platform of N-acetyl-glucosamine (GlcNAc) loaded silk hollow spheres embedded in silk hydrogel for in situ therapeutic release and enhanced mechanical strength. The assembled silk hydrogel provided adequate structural support to the ex vivo degenerated disc model in a cyclic compression test at par with the native tissue. Spatiotemporal release of GlcNAc in a controlled manner from the silk hollow microspheres trigger enhanced proteoglycan production from ADSCs embedded in the composite system. Role of MAPK and SMAD pathways in increasing proteoglycan production have been explored by immunohistological analysis as a result of the action of GlcNAc on the cells, elucidating the potential of injectable silk microsphere-in-silk hydrogel for the regeneration of degenerated disc tissue.